Biodegradability enhancement of a pesticide-containing bio-treated wastewater using a solar photo-Fenton treatment step followed by a biological oxidation process - Vítor J. P. Vilar (2012)
This work proposes an efficient combined treatment for the decontamination of a pesticide-containing wastewater resulting from phytopharmaceutical plastic containers washing, presenting a moderate organic load (COD = 1662-1960 mg O-2 L-1; DOC = 513-696 mg C L-1), with a high biodegradable organic carbon fraction (81%; BOD5 = 1350-1600 mg O-2 L-1) and a remaining recalcitrant organic carbon mainly due to pesticides. Nineteen pesticides were quantified by LC-MS/MS at concentrations between 0.02 and 45 mg L-1 (14-19% of DOC). The decontamination strategy involved a sequential three-step treatment: (a) biological oxidation process, leading to almost complete removal of the biodegradable organic carbon fraction; (b) solar photo-Fenton process using CPCs, enhancing the bio-treated wastewater biodegradability, mainly due to pesticides degradation into low-molecular-weight carboxylate anions; (c) and a final polishing step to remove the residual biodegradable organic carbon, using a biological oxidation process. Treatment performance was evaluated in terms of mineralization degree (DOG), pesticides content (LC-MS/MS), inorganic ions and low-molecular-weight carboxylate anions (IC) concentrations. The estimated phototreatment energy necessary to reach a biodegradable wastewater, considering pesticides and low-molecular-weight carboxylate anions concentrations, Zahn-Wellens test and BOD5/COD ratio, was only 2.3 kJ uv L-1 (45 min of photo-Fenton at a constant solar UV power of 30 W m(-2)), consuming 16 mM of H2O2, which pointed to 52% mineralization and an abatement higher than 86% for 18 pesticides. The biological oxidation/solar photo-Fenton/biological oxidation treatment system achieved pesticide removals below the respective detection limits and 79% mineralization, leading to a COD value lower than 150 mg O-2 L-1, which is in agreement with Portuguese discharge limits regarding water bodies.